Leveraging active learning practices for effectiveness of higher education: performance based investigation - Vignesh Saravanan Kirubakaran; Swarna Sudha Muppudathi; Jothi Thilaga Paul Ayyadurai; Sakthi Priya Gomathi Nayagam (Institute of Advanced Engineering and Science, 2025)
Engineering graduates in India struggle with employability due to outdated curricula and ineffective teaching methods, which limit their ability to apply knowledge and think critically. A performance-based study investigated the impact of active learning (AL) techniques in technical education using methods like concept mapping, role-playing, virtual labs, and collaborative coding in computer science and engineering courses. The findings showed a 35% to 40% improvement in academic results compared to traditional methods, along with significant boosts in student engagement, comprehension, and critical thinking. Student feedback and performance evaluations strongly favored AL. Cluster analysis revealed fewer slow learners, highlighting its effectiveness in meeting diverse needs. The study concludes that integrating AL can better prepare students for the job market and enrich their educational experience.